MONARCH BUTTERFLY - Gibbons, Gail (New York : Holiday House, 2021)
"The life cycle of the monarch butterfly begins when it is a tiny egg clinging to a leaf. In time, it goes through a transformation called metamorphosis to become a butterfly, and in the fall, it can migrate almost 100 miles each day. In this book, follow the story of one monarch butterfly and learn about what it eats, how it grows, and more."--Dust jacket flap
Keywords: Monarch butterfly -- Juvenile literature; Monarch butterfly -- Life cycles -- Juvenile literature; Monarch butterfly; Instructional and educational works; Juvenile works